Dissociating the Electrophysiological Correlates between Item Retrieval and Associative Retrieval in Associative Recognition: From the Perspective of Directed Forgetting - Wang, Yujuan; Mao, Xinrui; Li, Bingbing; Wang, Wei; Guo, Chunyan (Frontiers in Psychology, 2016)
Although many behavioral studies have reported associative memory was different from item memory, evidence coming from ERP researches has been in debate. In addition, directed forgetting effect for items has been fully discussed, but whether association between items can be directed-forgotten was unclear. The directed forgetting effect was important for disassociating the item retrieval and associative retrieval because of the one-to-one mapping relationship both between item retrieval and familiarity and between associative retrieval and recollection Thus, the aim of this study was to investigate the dissociation between item retrieval and associative retrieval and test directed forgetting effect for associative information. Associative recognition paradigm combined with directed forgetting paradigm by ERP recording was employed. Old/rearranged effect in to-be-remembered condition, which was associated with associative memory, was significant at 500-800 ms (LPC) but not at 300-500 ms interval (FN400), indicating that item information was retrieved prior to associative information. The ERP wave calculated by subtracting the to-be-forgotten old pairs with “old” response from those with “rearranged” response, which reflected associative retrieval in the to-be-forgotten condition, was negative from 500 to 800 ms (reversal old/new effect), indicating that association between items can be directed-forgotten. Similar evidence was obtained by contrasting “rearranged” responses aimed to the to-be-forgotten old pairs with those aimed to the to-be-remembered rearranged pairs, which actually represented the complete failure of associative retrieval. Therefore, item retrieval and associative retrieval were indexed by FN400 and LPC respectively, with associative retrieval more inhibited than item retrieval.